The Red Fruit (Pandanus Conoideus Lam) Ethanol Extract Decreased the Nitric Oxide (NO) Levels of Plasmodium Berghei Infected Swiss Mice Malaria Model but not the Interferon Gamma (IFN-γ) - Mujur Mujur; Demianus Tafor; Widya Wasityastuti; Achmad Djunaidi; Eti Sholikhah Nurwening (Pusat Kedokteran Tropis, 2013)
ABSTRACTIntroduction: The immunity against malaria infection was very complex, involving humoral immunity and cellular immunity. One of the methods to improve body immune response was using antioxidant. Red fruit (Pandanus conoideus Lam) containing carotenoid and tocopherol that have antioxidants effects increase phagocytosis activity of macrophage and proliferation activity of lymphocyte as immune response againts parasite infection.Objectives: This study was intended to know the effect of red fruit (P. conoideus Lam) ethanol extract on IFN-γ and nitric oxide (NO) levels in Plasmodium berghei infected Swiss mice malaria model.Methods: This quasi experimental study used post test only control group design. Sixty eight-week aged male Swiss mice were devided into 6 groups. Group I was not given red fruit ethanol extracts neither infected by P.berghei, group II was given 260mg/kg/day of red fruit ethanol extracts, and it was not infected by P.berghei, groups III, IV and V were given red fruit ethanol extracts at 130, 260 and 520mg/kg/day respectively and infected by P.berghei. Group VI was not given the extract, however it was infected by P.berghei as control group. The red fruit ethanol extracts or the carrier was given for 28 days and the mice were infected by P.berghei in the beginning of week 3. On the day 3 and 9 after infection, 2 mL blood was taken from 3 mice of each group for serum isolation.Results: There was not any significant difference (p>0.05) mean of IFN-γ levels in all groups neither on day 3 nor day 9 after infection. The nitric oxide levels mean of mice group which have received red fruit extracts at 130 and 260mg/kg/day on the day 9 and in mice group which have received red fruit extracts 260mg/kg/day on day 3 were lower than they were in control group without any extract (group VI). However, the nitric oxide levels mean of mice group which have received 520mg/kg/day did not show any significant difference (p>0.05) compared with control group.Conclusion: The red fruit (P. conoideus Lam) ethanol extract did not show any significant effect on the IFN-γ levels, however at doses of 130 and 260mg/kg/day it decreased the nitric oxide level of P. berghei infected Swiss mice malaria model significantly. Keywords: Pandanus conoideus Lam, Interferon gamma (INF-γ), Nitric oxide (NO), Plasmodium berghei, and Malaria ModelKeywordsPandanus conoideus Lam, Interferon gamma (INF-γ), Nitric oxide (NO), Plasmodium berghei, and Malaria Model